2018
DOI: 10.1097/cnq.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nurse-Led Intervention on Patients' Anxiety and Sleep Before Coronary Artery Bypass Grafting

Abstract: The aim of this study to examine the effects of supportive-educational nurse-led intervention on the patients' anxiety and sleep before the coronary artery bypass grafting.The current clinical trial recruited 160 patients (N = 160) waiting for the coronary artery bypass grafting by random block sampling and divided them into two 80-people experimental and control groups. Spielberger's State Anxiety Inventory was completed on the first day. The Groningen's Sleep Quality Index was also completed by the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
0
29
0
5
Order By: Relevance
“… 32 , 37 , 38 , 49 , 53 , 54 , 57 , 58 , 59 , 63 , 70 , 71 , 79 , 81 , 91 , 93 , 94 , 103 , 105 , 108 Prevention of anxiety was a secondary outcome of interest in a further nine (10%) studies. 22 , 23 , 25 , 47 , 50 , 55 , 69 , 73 , 80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32 , 38 , 53 , 57 , 59 , 71 , 81 , 94 , 105 nine were focused on pediatric patients, 37 , 49 , 54 , 63 , 79 , 91 , 93 , 103 , 108 (with four of these also including caregivers as a sub-population, 37 , 49 , 54 , 108 and another focused on adolescents 37 ); one study concentrated solely on caregiver (parent) anxiety. 70 The interventions of interest included music; 32 , 58 , 59 , 71 , 103 education (including videos); 37 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 , 37 , 38 , 49 , 53 , 54 , 57 , 58 , 59 , 63 , 70 , 71 , 79 , 81 , 91 , 93 , 94 , 103 , 105 , 108 Prevention of anxiety was a secondary outcome of interest in a further nine (10%) studies. 22 , 23 , 25 , 47 , 50 , 55 , 69 , 73 , 80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32 , 38 , 53 , 57 , 59 , 71 , 81 , 94 , 105 nine were focused on pediatric patients, 37 , 49 , 54 , 63 , 79 , 91 , 93 , 103 , 108 (with four of these also including caregivers as a sub-population, 37 , 49 , 54 , 108 and another focused on adolescents 37 ); one study concentrated solely on caregiver (parent) anxiety. 70 The interventions of interest included music; 32 , 58 , 59 , 71 , 103 education (including videos); 37 ,…”
Section: Resultsmentioning
confidence: 99%
“…Prevention of anxiety, both from the patient and caregivers' perspective, was the most common primary outcome of interest, accounting for over a fifth of studies (n=20, 23%). 32,37,38,49,53,54,57,58,59,63,70,71,79,81,91,93,94,103,105,108 Prevention of anxiety was a secondary outcome of interest in a further nine (10%) studies. 22,23,25,47,50,55,69,73,80 Of the studies including anxiety prevention as the primary outcome, nine studies (47%) were focused on adult patients; 32,38,53,57,59,71,81,94,105 nine were focused on pediatric patients, 37,49,54,63,79,91,93,103,108 (with four of these also including caregivers as a sub-population, …”
Section: Prevention Of Caregiver and Patient Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…The participants were asked to write their demographic information, including name, age, gender, marital status, race, education, access number, disease, type of cancer treatment in the beginning. The translated (Farsi) Groningen Sleep Quality Scale (GSQS), Pittsburgh sleep quality index (PSQI), Hamilton Rating Scale for Depression (HRSD), and Hamilton Anxiety Rating Scale (HARS) were used according to previously published paper (Jafarian, Gorouhi, Taghva, & Lotfi, 2008;Mousavi Malek, Zakerimoghadam, Esmaeili, & Kazemnejad, 2018;Tanner et al, 2013). To assess the appropriation of translated entries, a consultation was done with a bilingual neurologist and psychiatrist, who confirmed the validity of the translated questionnaires.…”
Section: Data Gathering and Questionnairesmentioning
confidence: 99%
“…The intervention focused on patients’ specific needs and fears and the authors concluded that healthcare professionals should be trained to better provide patients with emotional support before undergoing cardiac surgery to reduce preoperative anxiety. In another RCT, a nurse-delivered “supportive educational” intervention (comprising procedural information regarding the surgery, encouraging patients to discuss anxiety, fear and its causes, and training of relaxation techniques such as deep breathing) reduced patients’ anxiety and improved patients sleep quality before undergoing CABG surgery [ 47 ]. A supportive provider-patient interaction is considered an important and powerful mechanism with substantial influence on treatment outcomes [ 48 ].…”
Section: Interventions For Psychological Preparation Before Cardiac Smentioning
confidence: 99%